IMPROVING DATA LITERACY AMONG JOURNALISTS THROUGH WORKSHOP AND CONFERENCE TO ADVANCE THE ANALYTICAL SKILLS IN REPORTING - kusumawati, Utami diah; setianto, yearry panji (Universitas Pelita Harapan, 2024)
In an extraordinary situation such as pandemic and disaster, journalists perform a beneficial function in presenting accurate and reliable information. Information is passed on to the public who are in dire need of guidance during an emergency situation especially when the public is overloaded with unreliable information. Therefore, journalists have an obligation to present truth and eliminate disinformation by providing fact-based storytelling to the public as stated in one of the elements of journalism. The practice of data journalism has become popular as we are becoming more familiar with the presence of data as well as the development of technology. Thus, improving data literacy among journalists has become essential. The creation of Data and Computational Journalism Conference and Workshop Indonesia (DCJ-CI) 2022 aims to enhance the data skills of journalists nationwide by presenting a series of hands-on workshops, talk shows, seminars, and networking sessions to journalists, journalism students and lecturers, as well as data enthusiasts in Indonesia. This event was attended by hundreds of participants throughout the country and joined by speakers and experts from countries like U.S., England, India, Singapore, Nepal, and Indonesia. DCJ-CI resulted in data journalism and computational products published in several media in Indonesia.